Reassessing Diversion and Restorative Justice in Indonesia’s Juvenile Criminal System: Legal Paradigms, Policy Gaps, and Implementation Challenges - Heliany, Ina; Tjandrawinata, Raymond R (JURNAL AKTA, 2025)
Indonesia’s juvenile criminal justice system has embraced diversion and restorative justice as foundational principles following the enactment of Law No. 11 of 2012 on the Juvenile Criminal Justice System. This study critically examines the legal frameworks underpinning these principles, explores the policy gaps, and evaluates the implementation challenges that have emerged in practice. Employing a socio-legal qualitative methodology, this paper reviews statutory provisions, policy documents, and empirical research findings on diversion and restorative justice in Indonesia. The results reveal that while Indonesia’s legal reforms align with international standards on juvenile justice, significant inconsistencies persist in the practical application of diversion policies. Key barriers include uneven regional implementation, lack of standardized procedures, insufficient training for law enforcement, and societal resistance rooted in a punitive legal culture. The discussion offers a comprehensive analysis of these challenges and suggests strategic pathways to strengthen the restorative justice framework. The paper concludes by recommending policy reforms that incorporate local wisdom, enhance institutional capacity, and promote community involvement to ensure sustainable and effective juvenile justice practices in Indonesia.